2012
DOI: 10.1093/cid/cis758
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Meropenem in Infants With Suspected or Complicated Intra-abdominal Infections

Abstract: NCT00621192.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 18 publications
(21 reference statements)
5
43
0
2
Order By: Relevance
“…The high therapeutic outcomes reported in this study was constant with a results reported by Cohen et al, which found that the majority of patients treated with meropenem met the therapeutic success [21].…”
Section: Discussionsupporting
confidence: 89%
“…The high therapeutic outcomes reported in this study was constant with a results reported by Cohen et al, which found that the majority of patients treated with meropenem met the therapeutic success [21].…”
Section: Discussionsupporting
confidence: 89%
“…Conducting an adequately powered prospective safety study of ampicillin and measuring drug plasma levels would not be feasible in infants. An alternative, more focused approach to studying the safety of drugs in infants previously was published for the antibiotic meropenem(25, 26). …”
Section: Discussionmentioning
confidence: 99%
“…No other carbapenems have been approved by the U.S. Food and Drug Administration or European Medicines Agency for neonates or young infants Յ3 months of age, although investigations with meropenem have been conducted in neonates and are ongoing (6)(7)(8)(9). Meropenem is approved for bacterial meningitis or complicated intra-abdominal infections in adults and infants aged Ͼ3 months, and ertapenem is approved for complicated intra-abdominal, urinary tract, and (sub)cutaneous infections, and community-acquired pneumonia in adults and children (Ͼ3 months) (6).…”
mentioning
confidence: 99%